2005
DOI: 10.1152/ajpcell.00112.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression and membrane localization of MCT isoforms along the length of the human intestine

Abstract: Recent studies from our laboratory and others have demonstrated the involvement of monocarboxylate transporter (MCT)1 in the luminal uptake of short-chain fatty acids (SCFAs) in the human intestine. Functional studies from our laboratory previously demonstrated kinetically distinct SCFA transporters on the apical and basolateral membranes of human colonocytes. Although apical SCFA uptake is mediated by the MCT1 isoform, the molecular identity of the basolateral membrane SCFA transporter(s) and whether this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
167
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(178 citation statements)
references
References 38 publications
9
167
1
1
Order By: Relevance
“…Fresh frozen original study by Garcia et al (9) demonstrated immunohistochemically the selective localization of MCT1 at the basolateral membrane of enterocytes in the cecum of hamsters, suggesting a role for MCT1 in the transport of monocarboxylates from the epithelium to the blood. However, subsequent studies using immunohistochemistry and the immunoblotting of purifi ed membrane fractions have reported the predominant localization of MCT1 in the luminal membrane of intestinal epithelial cells in humans (10,26), pigs (26), rats (29), and in a colonic cell line (3). At present, discussion on the functional signifi cance of MCT1 appears to be based on the apical localization of MCT1, as described in recent review articles (6, 13).…”
Section: Methodsmentioning
confidence: 99%
“…Fresh frozen original study by Garcia et al (9) demonstrated immunohistochemically the selective localization of MCT1 at the basolateral membrane of enterocytes in the cecum of hamsters, suggesting a role for MCT1 in the transport of monocarboxylates from the epithelium to the blood. However, subsequent studies using immunohistochemistry and the immunoblotting of purifi ed membrane fractions have reported the predominant localization of MCT1 in the luminal membrane of intestinal epithelial cells in humans (10,26), pigs (26), rats (29), and in a colonic cell line (3). At present, discussion on the functional signifi cance of MCT1 appears to be based on the apical localization of MCT1, as described in recent review articles (6, 13).…”
Section: Methodsmentioning
confidence: 99%
“…Colon > ileum, not in jejunum [24] MCT5 SLC16A4 N.R. Jejunum > colon [14] Colon > ileum, not in jejunum [24] MRP1 ABCC1 Ab Jejunum = ileum = colon [27] Jejunum, ileum > duodenum [28] Jejunum = colon [14] Duodenum [19] Jejunum [20] Small intestine [21,29] Colon [29,30] Small intestine and colon [31] Too low expression in jejunum, ileum and colon for protein determination [29] MRP2 ABCC2 Ex Jejunum > ileum > > colon [27] Duodenum > ileum > > colon [32] Duodenum = ileum > colon [16] Jejunum, ileum > duodenum [28] Duodenum > > colon [33] Jejunum > colon [18] Duodenum [19] Jejunum [16,20] Small intestine [21] Jejunum > ileum = colon [27] MRP3 ABCC3 Ab Colon > Ileum = duodenum [16] Jejunum, ileum > duodenum [28] Colon > jejunum [18] Duodenum [19] Jejunum [16,20] Small intestine [21,32] Colon [28,32] Small intestine and colon [29] MRP4 ABCC4 N.R.…”
Section: Intestinal Transporters For Organic Anions and Their Substramentioning
confidence: 98%
“…The direction of transport and the intestinal localization of the transporters are listed in Table 1. [13,17,22,[24][25][26][27][28]30,31,34,37] In the intestine, the absorptive transporters facilitate the absorptive permeability of drug substances and endogenous substances from the intestinal lumen into the mesenteric blood, whereas the exsorptive transporters will work to counteract the absorptive process and promote drug excretion into the gut lumen. Absorptive and exsorptive transporters are located at both the apical and the basolateral membrane.…”
Section: Intestinal Transporters For Organic Anions and Their Substramentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies suggest the existence of species differences and different transporter isoforms expressed in enterocytes along the intestine (67) . On the apical membrane of the epithelial cell, distinct transport mechanisms have been reported, i.e.…”
Section: Absorption Of Butyrate Scfa Membrane Receptor and Transportmentioning
confidence: 99%